The Effect of Changes in Tax Rates on Capital Structure - Amri Amrulloh; Yopie Diondy Kurniawan; Halleina Rejeki Putri Hartono; La Ode Abdullah (International Journal of Economics and Management Research, 2025)
This research aims to analyze the impact of changes in tax rates on corporate capital structure by highlighting how tax rate fluctuations affect financing decisions, particularly the balance between debt and equity. Using a literature review approach, the research examines various sources to identify patterns in the relationship between tax rates and capital structure, considering internal factors such as profitability, firm size, and access to external financing. The findings indicate that companies with high profitability and better access to funding are more flexible in adjusting their capital structure, while smaller or less profitable firms are more vulnerable to tax rate changes. This study contributes by offering a more holistic understanding of how tax policies influence financing decisions and emphasizes the importance of effective tax management strategies and stable tax policies. These findings have significant implications for policymakers and future research in developing relevant analytical models and strategies in the context of ever-evolving tax regulations.